2009
DOI: 10.1021/jp906409q
|View full text |Cite
|
Sign up to set email alerts
|

A Broadly Absorbing Perylene Dye for Solid-State Dye-Sensitized Solar Cells

Abstract: We present a new perylene sensitizer, ID176, for dye-sensitized solar cells (DSCs). The dye has the capability for very high photocurrents due to strong absorption from 400 to over 700 nm. Photocurrents of up to 9 mA cm -2 were achieved in solid-state DSCs employing the hole conductor 2,2′7,7′-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene (spiro-MeOTAD), with a conversion efficiency of 3.2%. In contrast, the sensitizer did not perform well in conjunction with liquid iodide/tri-iodide electrolytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 18 publications
4
80
0
Order By: Relevance
“…Additionally, the molecular structure of sensitizer can stabilize the dye and can provide a mean to control the interfacial behavior of electron transfer at TiO 2 /dye/electrolyte interface. 9,10 A substantial number of research techniques and computational tools have been employed already by different research groups to develop efficient sensitizers for the better power conversion efficiency (PCE) [11][12][13][14] than the existing ones. Pastore et al 3 reported ab initio approach to model different interface of DSSCs by DFT and TD-DFT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the molecular structure of sensitizer can stabilize the dye and can provide a mean to control the interfacial behavior of electron transfer at TiO 2 /dye/electrolyte interface. 9,10 A substantial number of research techniques and computational tools have been employed already by different research groups to develop efficient sensitizers for the better power conversion efficiency (PCE) [11][12][13][14] than the existing ones. Pastore et al 3 reported ab initio approach to model different interface of DSSCs by DFT and TD-DFT.…”
Section: Introductionmentioning
confidence: 99%
“…12 Environment friendliness and ease of fabrication make the later more prominent in the scientific community. Though a variety of metal-free organic dyes such as arylamine, 17,18 perylenes, 13 and anthocyanin dyes 19 have been explored, arylamine organic dyes (AOD) have received enormous attention in the last decade because of their high molar absorption coefficient and tunable donor-acceptor moieties. 17,18 The optimal performance of the solar cell is directed by multifaceted interactions between the device components and their multiple possible combinations that are experimentally challenging to address.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] for details on m esoporous TiO 2 electrode preparation, dye synthesis, electrolyte preparation, solar cell assembly and solar cell characterization.…”
Section: Methodsmentioning
confidence: 99%
“…[9] A compelling result obtained within CMD research is that some perylene-based dyes performed much better in solid-state DSCs using spiro-MeOTAD than in standard iodide / triiodide electrolyte-based DSCs. [10] This can be attributed to the much faster regeneration kinetics observed in solid-state DSCs.…”
Section: Design Synthesis and Characterization Of Dye Molecules For Dscmentioning
confidence: 99%
“…Most organic sensitizers absorb light below 600 nm while reasonably efficient near-IR/IR dyes used in DSSCs are only occasionally seen in literature. [24][25][26][27][28][29] Pentacene chromophores, with potential absorption out to 750 nm, 30 could extend the window of performance for DSSCs, provided that there is efficient coupling between the acene and the inorganic matrix. We report here the synthesis of a series of pentacene dyes ( Fig.…”
Section: Introductionmentioning
confidence: 99%